Evaluación de parámetros de sostenibilidad en proyectos de vivienda de interés social. Análisis del Conjunto Residencial El Porvenir, Matina. - Vargas-Brenes, Mario Alberto (Instituto Tecnológico de Costa Rica, 2017)
This document establishes an evaluation mechanism in terms of sustainability, applicable to projects of social housing or low cost home buildings. The methodology is chosen after the comparison of several characteristics of the main existing systems at national and international level, obtained from worldwide literature in this subject. The methodology of evaluation used is calibrated for the specific conditions of the country and the type of building to be evaluated, to be subsequently applied in the evaluation of the Conjunto Residencial El Porvenir, a social housing project completed in 2014 for 230 families in the province of Limon, specifically at Matina's canton. The adjustment involve the consulting of national and international regulations, typical yields of similar buildings, as well as the criteria of experts on the subject of sustainable construction and development of social housing projects. After the evaluation of the Conjunto Residencial in its design and operation phase, made with 65 and 63 indicators respectively, the application of some good practices to achieve sustainability in this type of projects was evidenced, but also the recurrent presence of several deficiencies. Based on the results obtained, a series of improvement proposals are made for the Conjunto Residencial El Porvenir itself, as well as for other similar projects to be developed in other points of the Caribbean region of Costa Rica.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2017.
Keywords: Sostenibilidad; Viviendas; Evaluación; Construcción sostenible; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture